Student to Faculty Incivility : Experience of Faculty in Higher Education Institutions and its Consequences - Vashisht, Sakshi; Vashisht, Ravi (Prabandhan: Indian Journal of Management, 2020)
Uncivil behavior of students has a significant impact on the faculty members. Information regarding students’ incivility and its implications on faculty in private higher education institutions of India is insufficient. Therefore, the present study examined the relationship between uncivil behaviours of students and work engagement of faculty participants. The study also explored the relationship between work engagement and turnover intentions and work engagement and career commitment of faculty staff. One hundred and twenty faculty members were approached, of which 102 agreed to participate in the study. A total of 75 respondents completed the questionnaire for a response rate of 73%. Of the total participants, 74% were female (n = 56) and 26% were male (n = 19). Participants ranged in age from 22–48 years of age (mean = 36, standard deviation = 7.71). Forty eight percent of the respondents were from humanities and social sciences, 22% from engineering, 12% from law, and rest 18% from others. The data collected were analyzed with the help of SPSS 21 using descriptive and inferential statistics. The study found that uncivil behavior of students, both within and outside the classroom boundaries, had a significant impact on the dimensions of work engagement, that is, vigor, dedication, and absorption and on the overall work engagement of faculty members. Furthermore, a significant relationship was observed between work engagement and turnover intentions and career commitment.